2018
DOI: 10.1002/admi.201800661
|View full text |Cite
|
Sign up to set email alerts
|

3D Hybrid Plasmonic Nanostructures with Dense Hot Spots Using Monolayer MoS2 as Sub‐Nanometer Spacer

Abstract: some problems for the use of graphene. First, it has been demonstrated that the intensity of the EF generally increase as the gap decreases from 10 nm to 6.2 Å but fall off dramatically when the gap further decrease from 6.2 Å for the occurrence of quantum mechanical effects based on the results of the simulation and experiments. [16] The thickness of monolayer graphene is just 3.4 Å, which is so thin that the quantum mechanical electron tunneling emerge in a NP/G/NP or NP/G/ metal film structure. For such nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…This ideal limit of detection (LoD) is four orders of magnitude improved in comparison with the individual 1T′ MoTe2 substrates, 11 and far surpasses the previously reported results on metal nanostructures hybridized with graphene, hBN, MoS2 and other 2D materials, whose fabrication processes are much more complicated, costly and time-consuming. 16,17,37,38 Detailed comparison between the present work and other plasmonic-2D material based SERS substrates can be found in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…This ideal limit of detection (LoD) is four orders of magnitude improved in comparison with the individual 1T′ MoTe2 substrates, 11 and far surpasses the previously reported results on metal nanostructures hybridized with graphene, hBN, MoS2 and other 2D materials, whose fabrication processes are much more complicated, costly and time-consuming. 16,17,37,38 Detailed comparison between the present work and other plasmonic-2D material based SERS substrates can be found in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…A spacing of 1 nm or less may relate, in praxis, to the use of small biomolecules such as cysteamine [ 29 ] and DNA-assisted assemblies [ 30 ] to generate sub-nanometer gaps between metallic structures. Other studies have demonstrated the deposition of monolayers such as graphene [ 44 , 45 ] and MoS 2 [ 46 ] as sub-nanometer spacers between NP-NP structures. In real-world applications, such as the sensing of drugs [ 47 ], pollutants [ 48 ], and cancer diagnosis [ 49 ], having an e-field enhancement over large matrix volumes is highly desirable as it increases the probability of detection [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…MoS 2 / graphene heterostructure, serving as nanospacer, could avoid the quantum mechanical electron tunneling current, forming high-density hot spots. [103,104] These substrates could provide electron transfer between MoS 2 and metal NPs accompanied by thickness-controlled plasmonic coupling between two noble metal surfaces (Figure 13d). [103] However, the application of sandwich-like substrate has not yet been tested on real analyte sensing.…”
Section: Novel Multicomponent Architecturementioning
confidence: 99%
“…[103,104] These substrates could provide electron transfer between MoS 2 and metal NPs accompanied by thickness-controlled plasmonic coupling between two noble metal surfaces (Figure 13d). [103] However, the application of sandwich-like substrate has not yet been tested on real analyte sensing.…”
Section: Novel Multicomponent Architecturementioning
confidence: 99%